KARAKTERISTIK MARSHALL CAMPURAN ASPAL PORUS DENGAN PEMANFAATAN LIMBAH BONGGOL JAGUNG SEBAGAI FILLER - Pramanda, Firzi Abi; Hartatik, Nurani; Rizkiardi, Aditya; Prasetyo, Yudi D (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
Porous asphalt is a mixture of hot asphalt with an open gradation, characterized by a high proportion of coarse aggregates and a low proportion of fine aggregates, creating large air voids of around 18% - 25% in the mixture structure. These air voids are designed to allow water flow during rain, thus reducing the occurrence of surface water pooling on roads. Currently, porous asphalt is being developed as an alternative material for the construction of wearing courses. This study aims to analyze the use of corn cob waste as a filler in porous asphalt mixtures. The study tests the optimum asphalt content (OAC) in mixtures using corn cob ash filler that passes through a No. 200 sieve (0.075 mm) by 1%, with variations of asphalt content at 4%, 4.5%, 5%, 5.5%, and 6%. The determination of optimum asphalt content follows the guidelines set by the Bina Marga Specifications (Revision 2, 2018) and the Australian Asphalt Pavement Association (AAPA 2004), using three main parameters: Marshall, Cantabro Loss (CL), and Asphalt Flow Down (AFD). The results showed that the values of the three main parameters, namely Void in Mixture (VIM) at asphalt contents of 4% - 4.5% (20.81% and 18.25%), met the required range of 18% - 25%, Cantabro Loss (CL) at asphalt contents of 4.5% - 6% (29.10%, 23.61%, 18.69%, 14.29%) met the requirement of ? 35%, and Asphalt Flow Down (AFD) at 4% - 4.5% (0.15% and 0.25%) met the requirement of ? 0.3. The optimum asphalt content (OAC) in this study was found to be 4%.